Relationship between Corporate Governance and Voluntary Disclosure in Annual Reports: Evidence from Listed Companies in China and UK - Chang, Siqi (2012)
Corporate voluntary disclosure has been extensively documented across markets, such as in the U.S., UK and Asian region. This current dissertation investigates the different voluntary disclosure level of listed companies between China and UK as well as the interplay between corporate governance and voluntary disclosure. I regressed voluntary disclosure index of three different information types (strategic information, financial information and non-financial information) on five governance variables (board size, presence of audit committee, ownership concentration, board composition and CEO duality) and three control variables (firm size, leverage and profitability) with data collected from corporate annual reports of 100 listed companies in Food & Beverage industry.